Case-based educational intervention to assess change in providers' knowledge and attitudes towards the 2013 American College of Cardiology/American Heart Association Cholesterol Management Guideline. (March 2016) - Pokharel, Yashashwi; Steinberg, Lynne; Chan, Winston; Akeroyd, Julia M.; Jones, Peter H.; Nambi, Vijay; Nasir, Khurram; Petersen, Laura; Ballantyne, Christie M.; Virani, Salim S.
Abstract: Objective: Prior studies have shown provider-level knowledge gaps regarding the 2013 American College of Cardiology/American Heart Association guideline on the treatment of cholesterol and concerns about 10-year atherosclerotic cardiovascular disease (ASCVD) risk estimation. The effect of an educational intervention to mitigate knowledge gaps is unknown. Methods: We developed a questionnaire and administered it to providers before (pre-training) and after (post-training) a case-based educational intervention across 6 sites in Texas. The intervention highlighted the key recommendations of the 2013 guideline and the differences from the prior guideline mainly using clinical-vignettes. Several practice pertinent items were also discussed. Results: Most participants were providers-in-training (78%) in internal medicine (68%). Compared to pre-training, the post-training metrics were: 43% vs. 82% for providers' ability to identify 4 statin benefit groups; 47% vs. 97% for their awareness of the ASCVD risk threshold of ≥7.5% to initiate discussion about risks/benefits of statin therapy; 9% vs. 40% for awareness of differences between the Framingham and the ASCVD risk estimator; 26% vs. 78% for awareness of the definition of statin intensity; 35% vs. 62% for using a repeat lipid panel to document treatment response and adherence; and 46% vs. 81% for confidence in using the ASCVD risk estimator, respectively. Conclusions: A case-based educational intervention was associated with significant increase in providers' knowledge towards the 2013 cholesterol guideline, which could be related to the engaging nature of our intervention, using practice pertinent information and clinical vignettes. Such interventions could be useful in effective dissemination of the cholesterol guideline. Highlights: 2013 ACC/AHA cholesterol guideline was controversial and had sub-optimal adherence. We offered case based educational intervention to assess improvement in provider-level knowledge gaps. The intervention was associated with 16–53% absolute improvement in knowledge domain. There was 4–36% improvement in attitude domain. An engaging case based intervention can help in effective dissemination of the cholesterol guideline.